(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article scientifically analyzes the experience and priority traditions associated with the introduction of innovative educational technologies into the education system. Today, one of the strategic directions in education is defined as the main factor in the innovative activities of educational institutions. The article substantiates effective educational technologies used in teaching the science of labor law, and methods of their application in the classroom.